M1 Assertive outreach for persistent frequent attenders with copd in the community: reducing attendance by meeting their unmet psychological needs. (15th November 2017) - Chan, CSJ; Graham, L; Roots, D; Hodson, M; Sunak, S
Abstract : Introduction and Objectives: Co-morbid mental health problems in COPD can result in maladaptive and inappropriate utilisation of healthcare services (e.g., panic attacks cause attendance at A and E and acute hospital admission). Research evidence shows that COPD patients with co-morbid mental health problems have a higher rate of persistent A and E attendance and unplanned hospital admissions and on average incur an additional 80%–102% of medical treatment cost (Makek & Norris, 2008). Conventional models of mental health service provisions (e.g., Improving Access to Psychological Therapies (IAPT), secondary care mental health services) have proved ineffective in accessing and treating this subgroup of COPD patients. As such, there is a financial incentive for health services to develop more person-centred and cost-effective service models to address this issue. The current study investigates the effect of an Assertive Outreach Model of psychological interventions as applied to COPD patients with histories of frequent attendances to A and E and unplanned short-term hospital admissions. Attendance behaviours, depression and anxiety symptoms, and treatment costs were investigated. Methods: 19 COPD patients with persistently high attendance behaviours (i.e., three or more A and E attendances and/or two or more unplanned hospital admissions in a 12 month period) were identified from cross-referencing data from Electronic Patients Record (EPR) and the clinical knowledge of the community COPD team. They were then proactively engaged in an assertive outreach model within two weeks of identification, and offered four to 12 sessions of community-based psychological intervention during a 24 month period. Results: Compared to their 12 month pre- psychological intervention baseline, a total reduction of 40% (n=56) A and E attendances and 33% (n=32) short-term inpatient admissions was seen which amounts to approximately £30 000 of cost savings on treatment per year. 16% (n=6) and 21% (n=8) of patients reported a significant reduction in their depression and anxiety. Conclusions: An Assertive Outreach model of psychological intervention for COPD and co-morbid mental health problems providing responsive community-based treatment is highly effective in reducing attendance behaviours, achieving cost-savings, and by implication improving quality of life. However, it does not significantly improve patients' mental health symptoms which is likely due to the complex and multiple needs of this patient group.